1995
DOI: 10.1063/1.114649
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous silicon–carbon based thin films with efficient ultraviolet-excited photoluminescence and low self-absorptivity in the emission spectral range

Abstract: Articles you may be interested inDiagnostics of the early phase of an ultraviolet laser induced plasma by spectral line analysis considering selfabsorption J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Plasma-polymerized organosilicone thin films have good optical and mechanical properties [2][3][4][5][6][7][8][9][10], which make them attractive candidates in many fields of applications such as scratch resistance coatings [5], humidity and chemical sensors [6,7], optical filters [8], protective coatings [9] and chemical barrier coatings [10]. Moreover, they seem to be very promising as silicon-based luminescent materials for optoelectronic devices [11]. It has been demonstrated that thin films deposited from hexamethyldisiloxane (HMDSO) or hexamethyldisilazane (HMDSN) combine the properties of efficient luminescence at room temperature and low absorptivity of the PL light [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma-polymerized organosilicone thin films have good optical and mechanical properties [2][3][4][5][6][7][8][9][10], which make them attractive candidates in many fields of applications such as scratch resistance coatings [5], humidity and chemical sensors [6,7], optical filters [8], protective coatings [9] and chemical barrier coatings [10]. Moreover, they seem to be very promising as silicon-based luminescent materials for optoelectronic devices [11]. It has been demonstrated that thin films deposited from hexamethyldisiloxane (HMDSO) or hexamethyldisilazane (HMDSN) combine the properties of efficient luminescence at room temperature and low absorptivity of the PL light [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they seem to be very promising as silicon-based luminescent materials for optoelectronic devices [11]. It has been demonstrated that thin films deposited from hexamethyldisiloxane (HMDSO) or hexamethyldisilazane (HMDSN) combine the properties of efficient luminescence at room temperature and low absorptivity of the PL light [11]. However, in contrast to other silicon-based luminescent materials, such as amorphous silicon, amorphous carbon and amorphous silicon-carbon alloys, little work has been devoted to the study of the PL properties of plasma-polymerized organosilicone films.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors explored the PL from similar films. Rüter et al [21] prepared luminescent waveguiding layer structures, in the spectral range of the luminescence emission (400-550 nm), on the bases of amorphous silicon-carbon based thin films deposited in a microwave plasma reactor, using organosilane vapors from liquid sources such as HMDSN. Seekamp et al [22] investigated the PL properties of plasma deposited films from liquid organosilicone precursors such as HMDS and HMDSN, where they found that the PL maximum varies between 490 nm and 410 nm, and attributed this PL to the existence of different chemical structures in the precursor such as Si-(CH 3 ) 2 , Si-(CH 3 ) 3 and Si-CH 2 -Si.…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…Various materials can be used for the fabrication of these detectors, such as SiC [1], Al x Ga 1--x N [2,3], diamond [4], Si or GaAs Schottky photodiodes with additional visible-cut off filter [5], amorphous SiCbased films [6], and NaCl : Eu 2+ and KCl 1--x Br x : Eu 2+ crystals [7,8].…”
Section: Introductionmentioning
confidence: 99%